2021
DOI: 10.1038/s41389-020-00294-8
|View full text |Cite
|
Sign up to set email alerts
|

YAP/TAZ inhibition reduces metastatic potential of Ewing sarcoma cells

Abstract: Ewing sarcoma (EwS) is a highly metastatic bone cancer characterized by the ETS fusion oncoprotein EWS-FLI1. EwS cells are phenotypically highly plastic and switch between functionally distinct cell states dependent on EWS-FLI1 fluctuations. Whereas EWS-FLI1high cells proliferate, EWS-FLI1low cells are migratory and invasive. Recently, we reported activation of MRTFB and TEAD, effectors of RhoA and Hippo signalling, upon low EWS-FLI1, orchestrating key steps of the EwS migratory gene expression program. TEAD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 59 publications
1
34
0
Order By: Relevance
“…In addition, EWS-FLI1 low cells are more chemoresistant, upregulate immune modulators PD-L1 and PD-L2, are resistant to T-cell mediated apoptosis, and upregulate angiogenic switch genes in response to Wnts [337,338]. We found MRTFB/YAP/TAZ/TEAD signaling as a master gene regulatory pathway specifically activated in EWSR1-FLI1 low cells [336], and treatment of EwS xenografts with the YAP/TAZ inhibitor verteporfin tended to reduce lung metastases in an orthotopic limb amputation xenograft mouse model [339]. In line, a recent study immunohistochemically identified an association of high YAP/TAZ expression with poor prognosis in a series of 55 tumors [340].…”
Section: Immunotargeting Of Ews Tumorsmentioning
confidence: 72%
See 2 more Smart Citations
“…In addition, EWS-FLI1 low cells are more chemoresistant, upregulate immune modulators PD-L1 and PD-L2, are resistant to T-cell mediated apoptosis, and upregulate angiogenic switch genes in response to Wnts [337,338]. We found MRTFB/YAP/TAZ/TEAD signaling as a master gene regulatory pathway specifically activated in EWSR1-FLI1 low cells [336], and treatment of EwS xenografts with the YAP/TAZ inhibitor verteporfin tended to reduce lung metastases in an orthotopic limb amputation xenograft mouse model [339]. In line, a recent study immunohistochemically identified an association of high YAP/TAZ expression with poor prognosis in a series of 55 tumors [340].…”
Section: Immunotargeting Of Ews Tumorsmentioning
confidence: 72%
“…Increasing tissue stiffness is a major component promoting transforming oncogene function [356], and one may therefore speculate that it also impacts on aggressiveness of bone metastatic disease. Hippo/YAP/TAZ signaling serves as the major cellular mechanosensor of the metastatic niche microenvironment, and increased YAP and TAZ protein expression and activity have recently been associated with low EWSR1-FLI1 levels and adverse disease outcome in EwS [336,339,340].…”
Section: Biological Concepts For Organotropism Of Ews Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…The following primary antibody was used for PLA assay: YAP (63.7; Santa Cruz Biotechnology), TEAD (D3F7L, Cell signaling). Cells were then subjected to proximity ligation assays using the Duolink™ In Situ Red Starter Kit Mouse/Rabbit (DUO92101; Sigma-Aldrich/Merck) and following the manufacturer's instructions [58].…”
Section: Proximity Ligation Assay (Pla)mentioning
confidence: 99%
“…Recent findings in Ewing sarcoma demonstrated that TEAD triggers cytoskeletal riorganization in cells characterized by low levels of EWS-FLI1 fusion protein [235] and this is relevant considering that there are data indicating that low EWS-FLI1 levels might promote Ewing sarcoma migration, invasion and metastasis [228]. Published data suggested that TAZ might play a relevant role in metastatic onset [235].…”
Section: Hippo Pathwaymentioning
confidence: 99%